Liquidity dependencies in the euro area - Carla Soares (European Central Bank (ECB), 2025)
This study investigates to what extent the significant liquidity injections by the ECB over the past 15 years may have created a dependency by banks on central bank liquidity itself. Following Acharya et al. (2024), I examine whether the ECB's liquidity provision changed banks' incentives to increase liquid deposits, potentially heightening their susceptibility to liquidity shocks. Using both aggregate and bank-level data, I find that euro area banks tend to increase demand deposits and decrease time deposits with their holdings of excess reserves over the liquidity expansion phase and do not revert when aggregate liquidity starts to shrink. However, this is contained to specific periods, when interest rates were low and stable. The differences relative to the US could be related to distinct sources of liquidity and regulatory frameworks governing liquidity.
Keywords: E5; G21; 330; Monetary policy; central bank liquidity; deposits; euro area